Modified broth-disk surveillance of clindamycin-resistant Bacteroides fragilis group. - Zar, F A (1983)
The modified broth-disk susceptibility test was used to assess the incidence of clindamycin resistance in the Bacteroides fragilis group. Over a 34-month period, 544 isolates were tested, 21 (4%) of which were found to be resistant. There was no significant difference in resistance among the six species, and resistance did not increase with time. In a 12-disk assay, the concentrations of clindamycin achieved approximated the concentrations expected (expected breakpoint, 4.8 micrograms/ml).